Photochemical In Situ Exfoliation of Metal–Organic Frameworks for Enhanced Visible‐Light‐Driven CO2 Reduction - Zheng, Hui‐Li; Huang, Shan‐Lin; Luo, Ming‐Bu; Wei, Qin; Chen, Er‐Xia; He, Liang; Lin, Qipu (Angewandte Chemie International Edition, 2020)
Two novel two‐dimensional metal–organic frameworks (2D MOFs), 2D‐M2TCPE (M=Co or Ni, TCPE=1,1,2,2‐tetra(4‐carboxylphenyl)ethylene), which are composed of staggered (4,4)‐grid layers based on paddlewheel‐shaped dimers, serve as heterogeneous photocatalysts for efficient reduction of CO2 to CO. During the visible‐light‐driven catalysis, these structures undergo in situ exfoliation to form nanosheets, which exhibit excellent stability and improved catalytic activity. The exfoliated 2D‐M2TCPE nanosheets display a high CO evolution rate of 4174 μmol g−1 h−1 and high selectivity of 97.3 % for M=Co and Ni, and thus are superior to most reported MOFs. The performance differences and photocatalytic mechanisms have been studied with theoretical calculations and photoelectric experiments. This study provides new insight for the controllable synthesis of effective crystalline photocatalysts based on structural and morphological coregulation. As a result of rational structural design and structure‐directed morphology control, two new 2D MOFs underwent photochemically assisted in situ exfoliation to form nanosheets during visible‐light photocatalytic CO2 reduction (see picture). The exfoliated nanosheets displayed a high CO evolution rate and high selectivity for the formation of CO.